Pengurangan Cacat Bagian Panel Atap dalam Proses Pengiriman Ekspor Menggunakan Metode DMAIC: Studi Kasus di Produsen Otomotif - Setiawan, Indra; Setiawan, Setiawan (Jurnal Sistem dan Manajemen Industri, 2020)
Product quality has now become one of the main factors that every company must have to compete globally. One way is to reduce the number of defective products in the production process. This method is a continuous improvement effort made by PT Toyota Motor Manufacturing Indonesia and companies engaged in the automotive sector that produces cars. One of the processes is packing roof panels whose output will be sent to importing countries where the number of requests per month is relatively high but still has a high defect rate. Based on production data and defect data for the January-February 2019 period, roof panel packaging production has a 1% -3% defect rate. This company must reduce the defect rate to achieve the company target of zero defects. This study aims to improve the quality of the packaging process by minimizing the number of defective products. This study uses the Six Sigma method with DMAIC phases. This method has several phases, namely, Define, Measure, Analysis, Improvement, and Control. Corrective action to reduce product defects based on 5W + 1H is to formulate a repair plan at the upgrade phase, namely by making SOPs spraying anti-rust and supervising operators who produce roof panel packaging. The improvement results reduced the DPMO value from 33,500 units to 2,050 units and increased the sigma level from 3.33 to 4.37. The DMAIC phase effectively controls and improves product quality levels in the automotive industry.